Éditorial - El Houdaïgui, Rachid; del Valle Gálvez, Alejandro; Acosta Sánchez, Miguel (PEACE & SECURITY-PAIX ET SÉCURITÉ INTERNATIONALES (EuroMediterranean Journal of International Law and International Relations), 2018)
Éditorial